2014
DOI: 10.1097/hco.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

The talk test

Abstract: The talk test is a valid, reliable, practical and inexpensive tool for prescribing and monitoring exercise intensity in competitive athletes, healthy active adults and patients with cardiovascular disease. Healthcare professionals should feel comfortable in advocating its use in a variety of clinical and health-promotion settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 34 publications
1
49
0
1
Order By: Relevance
“…Because the site audits were conducted at a single point in time, it is possible that the fitness leaders frequently encourage daily aerobic exercise, but it was not observed during the audited class specifically. With regard to the latter, there are several practical methods for self-monitoring exercise intensity that are routinely presented in the HWE Training Program for fitness leaders, including heart rate monitoring, the Borg Rating of Perceived Exertion and the Talk Test [ 18 – 20 ]. Audit findings were provided to the facilities, and therefore it is hoped that this feedback will result in improvements in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Because the site audits were conducted at a single point in time, it is possible that the fitness leaders frequently encourage daily aerobic exercise, but it was not observed during the audited class specifically. With regard to the latter, there are several practical methods for self-monitoring exercise intensity that are routinely presented in the HWE Training Program for fitness leaders, including heart rate monitoring, the Borg Rating of Perceived Exertion and the Talk Test [ 18 – 20 ]. Audit findings were provided to the facilities, and therefore it is hoped that this feedback will result in improvements in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…52 It has been suggested that the 6-minute walk test is a simple and reliable test to estimate exercise tolerance in patients with CHF; however, it is not a valid tool for prescribing exercise intensity. 53,54 Despite relatively limited literature, available studies are consistent in showing that low to moderate intensity aerobic physical activity improves exercise capacity, QoL and performance in activities of daily living in patients with AF. 55,56 However, some authors recommend training for patients with CHF at the RCP level (i.e.…”
Section: Intensity Duration Frequency and Modality Of Trainingmentioning
confidence: 98%
“…Following the line of Wirtz et al [39], the absolute load was increased by 5% every two weeks to apply the principle of progressive overload. After strength exercises, participants performed a 10-min cardiovascular work on a treadmill, at a constant individualized speed, obtained from the talk test [40] (i.e., the highest speed they could walk while talking). The intensity of cardiovascular training was increased by 5% every week.…”
Section: Interventionsmentioning
confidence: 99%